Pengaruh Kepemimpinan dan Motivasi Terhadap Kinerja Karyawan Pada PT Eka Mas Republik Branch Makassar - sangtutu, savitri saraswati; Irfan, Andi; Ansar (Jurnal Online Manajemen ELPEI, 2025)
This study aims to determine the effect of leadership and motivation on employee performance at PT Eka Mas Republik Branch Makassar. The object of this study is PT. Eka Mas Republik which is engaged in the FTTH sector. This study uses a qualitative descriptive method to examine more deeply about leadership and motivation. The respondents as samples in this study were employees at PT Eka Mas Republik totaling 30 people. The results of this study indicate that there is a partial and simultaneous influence of leadership and work motivation on employee performance.